Guiding users to the right sources virtually/ Haslinda Mohamed, Saidatul Akmar Ismail and Nor Rashimahwati Tarmuchi - Mohamed, Haslinda; Ismail, Saidatul Akmar; Tarmuchi, Nor Rashimahwati (Fakulti of Information Management, Universiti Teknologi MARA, 2015)
This is a case study to explore the practices of reference services at a university library. The study is conducted to understand more about the current practices of reference services, particularly through electronic mediums at the campus, to identify issues faced by the librarians in supporting those users' demands, and to provide several recommendations. The study has revealed that the services they provide through electronic mediums to users can be improved to reduce manual management of questions and answers between the librarians and users. Some of the questions that the librarians receive everyday from their users could be avoided if proper database systems are available to store them for future retrieval. In addition, the library needs to revisit their policy and processes related to reference services to support virtual reference services. Reference librarians should give equal attention to enquiries directly from e mails as they would give to enquiries directly from users at the reference desk. They also need to be welI-trained and competent in using social media tools to take full advantage of the benefits offered by these technologies. The study has also resulted in the development of a system prototype to support virtual reference services.